2017
DOI: 10.1116/1.4984292
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of permeation of atmospheric gases through Viton O-ring gaskets for different initial conditions

Abstract: Viton O-ring gaskets are frequently used in high vacuum for demountable flange and vacuum valve seals. Atmospheric gases, particularly water vapor from humid air, permeate through Viton gaskets and thus limit the lowest attainable pressure level in vacuum systems. In this work, a comparison of a vacuum degassed Viton O-ring gasket and a gasket fully saturated with atmospheric gases was performed. A reference measurement with an alternative soft metal gasket for Klein Flange type flanges was also made. The perm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…After 96 hours of getter action argon has become the dominant residual gas component in the cryostat. The presence of a peak, with a.m. equal to 36 and corresponding to the isotope 36 Ar, clearly confirms the presence of argon, while the ratio of the peaks' amplitudes 36 40 = 9•10 −9 2.1•10 −6 •100% ≈ 0.4% is close to the tabular relative intense (0.3%) indicated in [25].…”
Section: Changing the Composition Of Residual Gases In A Cryostat Wit...supporting
confidence: 57%
“…After 96 hours of getter action argon has become the dominant residual gas component in the cryostat. The presence of a peak, with a.m. equal to 36 and corresponding to the isotope 36 Ar, clearly confirms the presence of argon, while the ratio of the peaks' amplitudes 36 40 = 9•10 −9 2.1•10 −6 •100% ≈ 0.4% is close to the tabular relative intense (0.3%) indicated in [25].…”
Section: Changing the Composition Of Residual Gases In A Cryostat Wit...supporting
confidence: 57%
“…In the subsequent CVE runs, the length of the SiNWs increased again to 9.8 μm and decreased gradually due to the residual supply of oxidant gases from the Viton gaskets. 36,37…”
Section: Resultsmentioning
confidence: 99%
“…In the subsequent CVE runs, the length of the SiNWs increased again to 9.8 mm and decreased gradually due to the residual supply of oxidant gases from the Viton gaskets. 36,37 To further investigate the role of oxidant gases on the morphology of the SiNWs, we used a Viton gasket to quantitatively control the concentration of oxidant gases during the CVE process. It has been reported that after 12 hours of baking at 200 1C, the relatively stable outgassing rate of Viton at 180 1C is estimated to be 2 Â 10 À8 Torr liter cm À2 s À1 .…”
Section: Materials Characterizationsmentioning
confidence: 99%
“…2 are from Chivers (water-liquid and steam), Ma (water vapor), and Sefa (water vapor) where the lines serve to guide the eye. [19][20][21] It is notable that permeability increases by ∼10× between room temperature and 150 °C, thereby demonstrating a strong temperature dependence. Water is of primary interest here because of its relatively high permeation rate through elastomer materials as well as its associated impact on background oxygen levels in a PEALD process environment.…”
Section: Resultsmentioning
confidence: 99%
“…3 to approximate the permeation rate of H 2 O through Viton. 21 In Fig. 3, the o-ring is compressed between two planar sealing surfaces forming an elliptical or oval shape.…”
Section: Resultsmentioning
confidence: 99%